1997
DOI: 10.1016/s0022-5347(01)64890-0
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Bone Growth After Ileal Augmentation Cystoplasty

Abstract: Acid challenged weanling rats that underwent ileal augmentation cystoplasty demonstrated decreased bone mineral density and growth compared to controls. These changes were prevented by bicarbonate replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 58 publications
3
7
0
Order By: Relevance
“…Only McDougal et al [28] found a minimal systemic acidosis in their rats, but without providing exact data or even significance levels; their observation that the administration of bicarbonate and ascorbic acid prevents a reduction of calcium content in bone‐ash studies, and decrease of bone density in dual‐photon absorptiometry (DPA), respectively (in an unknown proportion of animals), is usually used to support the assumption that even a minimal disturbance of the acid‐base‐balance may cause bone disease. Similar findings were published by Hochstetler et al [27], who stressed their augmented animals with ammonium chloride to mimic the human condition; when rats with augmentation cystoplasty given 1% ammonium chloride were supplemented with an equal molar diet of sodium bicarbonate, metabolic acidosis resolved and bone mineral density normalized to control values (with an unexplained discrepancy of bone mineral ash content and DEXA). Interestingly, Roth and Gasser [26] found no bone pathology in rats with respiratory compensated acidosis using up‐to‐date technology (DEXA, histomorphometry).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Only McDougal et al [28] found a minimal systemic acidosis in their rats, but without providing exact data or even significance levels; their observation that the administration of bicarbonate and ascorbic acid prevents a reduction of calcium content in bone‐ash studies, and decrease of bone density in dual‐photon absorptiometry (DPA), respectively (in an unknown proportion of animals), is usually used to support the assumption that even a minimal disturbance of the acid‐base‐balance may cause bone disease. Similar findings were published by Hochstetler et al [27], who stressed their augmented animals with ammonium chloride to mimic the human condition; when rats with augmentation cystoplasty given 1% ammonium chloride were supplemented with an equal molar diet of sodium bicarbonate, metabolic acidosis resolved and bone mineral density normalized to control values (with an unexplained discrepancy of bone mineral ash content and DEXA). Interestingly, Roth and Gasser [26] found no bone pathology in rats with respiratory compensated acidosis using up‐to‐date technology (DEXA, histomorphometry).…”
Section: Discussionsupporting
confidence: 85%
“…As the renal capacity to excrete acid loads is many times greater in rats than in man, while maintaining a normal or near‐normal serum pH, urinary diversion alone usually does not create detectable acidosis in these animals [25–27]. Only McDougal et al [28] found a minimal systemic acidosis in their rats, but without providing exact data or even significance levels; their observation that the administration of bicarbonate and ascorbic acid prevents a reduction of calcium content in bone‐ash studies, and decrease of bone density in dual‐photon absorptiometry (DPA), respectively (in an unknown proportion of animals), is usually used to support the assumption that even a minimal disturbance of the acid‐base‐balance may cause bone disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, ileocystoplasty in growing rats with no renal failure compromises bone mineralization predominantly in the cancellous compartment and can diminish the biomechanical properties of bone [8,12–14]. In growing rats with renal failure, ileocystoplasty can aggravate the reduced mineralization caused by uraemia [15] and have profound osteopenic effects on the trabecular architecture of bone, as reported here.…”
Section: Discussionmentioning
confidence: 67%
“…In previous studies we and others reported that the incorporation of an ileal segment into the bladders of growing rats with normal renal function leads to a reduced gain in bone density [8,12] and compromises the mineralization of the entire skeleton, resulting in osteopenia in the tibia and lumbar spine [13]. The loss of bone mass after ileocystoplasty can be associated with altered biomechanical properties, such as a reduced bone strength of the vertebral body [14].…”
Section: Discussionmentioning
confidence: 99%